Automatic controls for heating and air conditioning : principles and applications - Letherman, K. M. (International series in heating, ventilation, and refrigeration, 1981)
International Series in Heating and Ventilation, Volume 15: Automatic Controls for Heating and Air Conditioning: Principles and Applications details the relationship between theory and practice in implementing an automated system for thermal regulation.